2021
DOI: 10.3390/ijerph18073662
|View full text |Cite
|
Sign up to set email alerts
|

Training Habits of Eumenorrheic Active Women during the Different Phases of Their Menstrual Cycle: A Descriptive Study

Abstract: The purpose of this study was to examine the training habits of eumenorrheic active women during their menstrual cycle (MC), and its perceived influence on physical performance regarding their athletic level. A group of 1250 sportswomen filled in a questionnaire referring to demographic information, athletic performance and MC-related training habits. Of the participants, 81% reported having a stable duration of MC, with most of them (57%) lasting 26–30 days. Concerning MC-related training habits, 79% indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…It was once thought that the physiology of exercise was the same for both sexes, so the recommendations for sports practice in women have been widespread for a decade ( García-Pinillos et al, 2021 ). With women’s sport booming, the expectations of female players’ performance have increased and there has been a need to improve physiological knowledge of exercise in women, thus increasing the need for specific scientific research that can help in their performance ( Martínez-Lagunas et al, 2014 ; García-Pinillos et al, 2021 ). Nowadays, players are exposed to a greater amount of training and demand, therefore, it is necessary to understand the physiology of the players in order to design adequate training ( Pardos-Mainer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was once thought that the physiology of exercise was the same for both sexes, so the recommendations for sports practice in women have been widespread for a decade ( García-Pinillos et al, 2021 ). With women’s sport booming, the expectations of female players’ performance have increased and there has been a need to improve physiological knowledge of exercise in women, thus increasing the need for specific scientific research that can help in their performance ( Martínez-Lagunas et al, 2014 ; García-Pinillos et al, 2021 ). Nowadays, players are exposed to a greater amount of training and demand, therefore, it is necessary to understand the physiology of the players in order to design adequate training ( Pardos-Mainer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cycle is composed of the hypothalamic-pituitary-ovarian axis, with the secretion of gonadotropin-releasing hormone (GnRH) stimulating the release of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) which signal the ovaries to synthesize estrogen and progesterone ( Cable and Elliott, 2004 ; Brown et al, 2021 ). A normal menstrual cycle lasts about 28 days, and consists of a follicular phase typically lasting 12–14 days where estrogen levels are high and progesterone levels are low, an ovulatory phase that lasts 1–3 days with a rise in estrogen levels and a luteal phase that lasts 12–14 days with high levels of progesterone and medium levels of estrogen ( Draper et al, 2018 ; Dirk et al, 2020 ; García-Pinillos et al, 2021 ; Paludo et al, 2022 ). It has been demonstrated that estrogen can influence the cardiovascular system (including blood pressure, heart rate and rhythm, and vascular flow) as well as substrate metabolism ( Constantini et al, 2005 ), in practice, elevated estrogen levels are associated with lower blood lactate levels and longer times to exhaustion ( García-Pinillos et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From recreational to highly trained women, the effects of the menstrual cycle (MC) are present in their daily sports activities [1,2]. There are three distinctly hormonal environments that can be identified during the MC of eumenorrheic women: Low levels of estrogen and progesterone at the menstrual or early follicular phase (EFP), high and low levels of estrogen and progesterone at the preovulatory or late follicular phase (LFP), and high levels of estrogen and progesterone at the post-ovulatory or mid-luteal phase (MLP) [3].…”
Section: Introductionmentioning
confidence: 99%